Leukemia stem cells - Buß, Eike Christian; Ho, Anthony Dick (International journal of cancer, 2011)
Leukemia stem cells (LSCs) might originate from malignant transformation of normal hematopoietic stem cells (HSCs), or alternatively, of progenitors in which the acquired mutations have re-installed a dysregulated self-renewal program. LSCs are on top of a hierarchy and generate leukemia cells with more differentiated characteristics. While most leukemia cells are initially sensitive to chemo- and radiotherapy, LSCs are resistant and are considered to be the basis for disease relapse after initial response. Albeit important knowledge on LSC biology has been gained from xenogeneic transplantation models introducing human leukemia cells into immune deficient mouse models, the prospective identification and isolation of human LSC candidates has remained elusive and their prognostic and therapeutic significance controversial. This review focuses on the identification, enrichment and characterization of human LSC derived from patients with acute myeloid leukemia (AML). Experimental data demonstrating the clinical significance of estimating LSC burden and strategies to eliminate LSC will be summarized. For long-term cure of AML, it is of importance to define LSC candidates and to understand their tumor biology compared to normal HSCs. Such comparative studies might provide novel markers for the identification of LSC and for the development of treatment strategies that might be able to eradicate them.
Gesehen am 27.06.2022